Acoustic Emission in Elementary Processes of Friction and Wear: In-Situ Observation of Friction Surface and AE Signals - Alan HASE; Hiroshi MISHINA; Masaki WADA (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2009)
The relationship between acoustic emission (AE) signals and tribological phenomena in the elementary processes of friction and wear is examined. The elementary processes of friction and wear were observed by a frictional surface microscope, which installed a friction system into the view of an optical microscope. In this paper, the elementary processes are focused on the plastic deformation of the friction surface and the formation of wear particles between friction surfaces. In-situ experiments with the frictional surface microscope were performed by a pin-on-block type sliding test for iron and zinc. The friction surface and its side face were also observed by an atomic force microscope. The results show that two types of AE signals—a continuous AE signal of low amplitude and a burst-type AE signal of high amplitude—are detected in the elementary processes of friction and wear. The continuous AE signal of low amplitude is detected by the generation of slip lines and wear elements. The burst-type AE signal of high amplitude is detected by the formation of a transfer particle.